Establishing Controls and Auditing the Computerized Accounting System. (Book Review). - Meyer, Philip E.; Davis, Gordon B. (The Accounting Review, 1981)
Reviews the book "Establishing Controls and Auditing the Computerized Accounting System," by Elise G. Jancura and Robert V. Boos.